Elevated serum total immunoglobulin E is associated with an increased risk of lung cancer: a retrospective study - Zhou, Dongmei; Liu, Jia; Zhang, Chu; Kang, Dan; Kang, Jiayang; Meng, Zihan; Wang, Xiaonan (Frontiers in Immunology, 2025)
BackgroundThis study investigated the correlation between serum total IgE levels and the risk of lung cancer using univariate and multivariate logistic regression analysis.MethodsThis cross-sectional retrospective cohort study included clinical and laboratory data from 675 lung cancer patients and 1,193 healthy controls.ResultsThe lung cancer patients showed significantly higher serum total IgE levels compared to healthy individuals, with 47.9% of patients having IgE levels >100 IU/ml (P < 0.01). Higher serum total IgE levels (>100 IU/ml) were significantly associated with increased risk of lung cancer (OR=1.534, 95% CI: 1.203-1.957; P < 0.001). Multivariate logistic regression analysis results showed that age ≥65 years (OR=4.775, 95% CI = 3.478–6.555; P <0.001), smoking history (OR=1.719, 95% CI = 1.198–2.466; P =0.003), and an elevated lymphocyte-to-monocyte ratio (LMR) (OR=0.777, 95% CI = 0.678–0.890; P <0.001) were independent risk factors for lung cancer development in subjects with serum total IgE levels >100 IU/ml. The higher the serum total IgE level, the higher the T stage, N stage, M stage and the later the tumor clinical stage (all P <0.001). Survival analysis did not show statistically significant differences in the median progression-free survival (PFS) (P>0.05) or overall survival (OS) (P>0.05) among advanced lung cancer patients with different IgE levels (high and low).ConclusionLung cancer patients demonstrated elevated serum total IgE levels. Higher serum IgE levels were significantly associated with an increased risk of lung cancer. Therefore, serum total IgE level is a potential diagnostic biomarker for lung cancer. Moreover, IgE and its related allergic immune responses offer potential as innovative therapeutic targets in elderly lung cancer patients with an history of smoking and elevated monocyte counts.